Is the KKondae as a common psychological construct? Testing the KKondae scale with the U.S. sample, and the preliminary study of predictors and consequences of Kkondae - Jiyeon Lee; Dongwoo Ko; Hyoung-yong Choi (BMC Psychology, 2025)
Abstract Background The research aims to explore the common nature of ‘kkondae’—a Korean term denoting stubbornness—and its relevance across cultures, particularly examining the relationship between anxiety, kkondae tendencies, and resulting loneliness through difficulties in listening and acceptance in social interactions. Methods A sample of 454 individuals from the U.S. was surveyed online to assess the Korean-developed Kkondae scale’s reliability and validity. Structural Equation Modeling revealed that higher levels of anxiety might lead to increased loneliness, with kkondae traits acting as an intermediary. Results Anxiety was found to affect the tendency towards kkondae behavior, interfering with listening and effective communication, thus exacerbating loneliness. Conclusions Interpersonal communication issues are critical in increasing loneliness. This study adds a new dimension to loneliness research by linking the concept of kkondae with anxiety.